(untitled) (Research, Society and Development, 2021)
The Atlantic Forest is one of the main Brazilian biomes that extends from Rio Grande do Norte to Rio Grande do Sul. Within this ecosystem, stands out the formations of semi-deciduous seasonal forest Montana (marshes of altitudes). Therefore, the objective of the study was to investigate the floristic and phytosociological composition in a section of riparian forest of a fragment of Atlantic Forest in Ihumas, located in the municipality of Garanhuns - PE. The study was developed in a section of Mata Ciliar in the rural community of Inhumas, municipality of Garanhuns-PE. The area was delimited in 07 plots of 10 x 10 m, containing 0.07 ha of the total sampled area. In each plot were sampled all live arboreal individuals, with DAP 5 cm. In the fragment of Mata Ciliar in the Community of Inhumas, 257 tree individuals were found distributed in 14 families, 18 genera and 23 species. The families with the highest number of species richness were: Fabaceae (five ssp.), Sapindaceae (three ssp.) Myrtaceae and Melastomataceae (two ssp). The species Byrsonima sericea DC., Myrcia bela Cambess., Cupania impressinervia and Casearia sylvestris Sw. with an absolute frequency of 100%, 44% of the species classified as initial secondary and 73% have zoochoric dispersion. The area has high floristic richness being in the early phase of the successive development, being the species Cupania impressinervia Acev.-Rodr. the most represented in the sociological position of the arboreal vertical extract, occupying the three extracts.